How and Why Do Junior Doctors Study? What Materials Do They Use?. (6th February 2013) - Wiggins, Natasha; Haldar, Sananda; Biswas, Seema
Abstract : Context . Junior doctors studying for exams need reliable information close at hand. Objectives . We set out to understand the resources junior doctors use to study and revise. Methods . A questionnaire was circulated to junior hospital doctors within a single UK deanery sitting membership examinations, asking what motivates them to study, what resources they use to learn and revise, and what qualities they look for in the ideal learning and revision resource. Findings . We received a 70% response to the questionnaire (140 out of 200 doctors) and found that nearly all doctors are motivated to study by examinations (95%, n = 133 ) and by patients they look after on the wards (73%, n = 102 ). Their ideal learning resources comprise case-based learning (64%, n = 70 ). They use textbooks at least as much as online resources and learn directly from their seniors. Discussion and Conclusion . To tailor learning and revision resources for junior doctors we need nationwide research on how they learn and revise. This study supports the development of reliable case-based learning material in print and, and the collaboration of educators and junior doctors who have clear ideas about the resources they want to use.